TECHNICAL EVALUATION OF PEDESTRIAN FACILITIES ALONG THE PALEMBANG LRT LINE - Tri Mei Yuli; Betty Susanti; Melawaty Agustien (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The pedestrian path along the Palembang LRT line is one of the indispensable public facilities in Palembang city. Currently, the pedestrian path along the Palembang LRT has not functioned optimally, because the pedestrian path that should be intended for pedestrians but is often misused. In addition, the pedestrian paths are still not in accordance with the technical standards of pedestrian path planning. The purpose of this study was to evaluate pedestrian facilities along the Palembang LRT line. The research method is descriptive quantitative using an instrument to evaluate the existing condition of the pedestrian path based on the Circular Letter of the Minister of PUPR Regulation Number 18/Se/Db/2023. The results showed that of the 5 aspects used to evaluate, with 24 indicators, 13 indicators, amounting to 54.2 percent of pedestrian paths existed and met the technical criteria for pedestrian facilities, 10 indicators, amounting to 41.2 percent, existed but did not meet the criteria and 1 indicator, amounting to 4.2 percent, did not exist and did not meet the technical criteria for pedestrian facilities. To be able to optimize LRT, it is necessary to improve pedestrian facilities along the Palembang LRT to the maximum such as improving pedestrian path materials that meet the technical standards of pedestrian paths